Fascioliasis: A Rare Parasitic Infection-Mimicking Tumor in the Liver: Report of Two Cases - Samdanci, Emine; Sahin, Nurhan; Dagli, Adile Ferda; Akatli, Ayse Nur; Aydin, Nasuhi Engin (De Gruyter Poland Sp Zoo, 2019)
Fascioliasis is a rarely encountered parasitic infection in Turkey that mainly affects the liver and bile ducts. Other defined localizations of the parasite are the lungs, gastrointestinal system, and subcutaneous fatty tissue. Two cases of female patients who presented to the hospital with abdominal pain and whose physical examination and laboratory findings were normal except peripheral eosinophilia, were detected to have liver masses with necrotic areas. Segmental hepatectomies were performed in both cases with the preliminary diagnosis of liver tumors. Upon microscopic examinations of the resection materials, necrotic granulomatous inflammation with eosinophilic reaction at the periphery and the parasite (Fasciola hepatica) were seen. Both cases were reported to be fascioliasis according to these findings. Two cases of fascioliasis mimicking malignancy in the liver are presented here together with literature findings.
Keywords: Fascioliasis; Liver; Hepatectomy; Charcot-Leyden crystals